Synthesis and Characterization of Fe3O4 Composites Embeded on Coconut Shell Activated Carbon - Luqman Hakim; Endaruji Sedyadi (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Synthesis and characterization of Fe3O4-coconut shell activated carbon composites has been carried out to create a magnetic adsorbents. Composites were synthesized using the coprecipitation reflux method by mixing a solution of Fe3+/Fe2+ iron salt (mol ratio 2:1) and suspension of activated carbon in water followed by the addition of NaOH solution. The structure, functional groups, morphology and surface area of the composites were characterized using FTIR, XRD, SEM and GSA. The magnetic properties of composites are tested by response to magnetic fields. The characterization results showed that the embedment of Fe3O4 on coconut shell activated carbon was successfully carried out through the interaction of hydroxyl groups at wave numbers 601.79 and 416.62 cm-1. Diffraction peaks at 2θ 30.12° [220], 35.58° [311], 43.14° [400], 53.57° [422], 57.18° [511] and 62.83° [440] indicate the existence magnetite sized of 11.72 nm. Activated carbon has an average pore size of micropores with an average pore of 1.46 nm. Magnetite embedment reduced the surface area of activated carbon from 91.16 m2/g to 12.04 m2/g. The response of sample to the magnetic field indicates that composite has magnetic properties.